The respondent factors on the digital questionnaire responses - Muhardis Muhardis; Burhanuddin Tola; Herwindo Haribowo (REID (Research and Evaluation in Education), 2019)
Progress in the field of technology often facilitates human work. One of them is progress in the development of questionnaire modes. Currently, existing questionnaires have been based on a digital platform, which makes evaluators easy to design, disseminate, and conduct scoring. All are computer-based, making them reachable by the respondents no matter how far the location of the respondent is, as long as they are connected to the internet. However, any progress is accompanied by several obstacles. For example, the respondents experienced an error in responding to having the intent to respond 'Yes' option but pressing the 'No' button instead. It is very different from filling in paper and pencil based questionnaires in which they are sure to put a checkmark using a pencil on the answer choices. This problem is what the researchers found when distributing digital questionnaires to participants of the National Questions Writing Program based on the 'SIAP' (Sistem Inovatif Aplikasi Penilaian) application. On conditional questions (if you choose 'No', please stop), some respondents who have chosen 'No' answers still respond to the next questions. It causes the data obtained are unreliable. After conducting a more in-depth analysis, the researchers found that respondents’ factors as psychological factors are the cause, such as the new experience of accessing applications, understanding of applications, stress, and personal health. Uniquely, the respondents who have problems are those in the context of productive age, i.e 30 to 39 years old, more than five years of teaching experience, postgraduate level, and female.